A molecular defect in hepatic cholesterol biosynthesis in sitosterolemia with xanthomatosis. - Nguyen, L B (1990)
We examined the relationship between cholesterol biosynthesis and total and high affinity LDL binding in liver specimens from two sitosterolemic and 12 healthy control subjects who died unexpectedly and whose livers became available when no suitable recipient for transplantation was identified. Accelerated atherosclerosis, unrestricted intestinal sterol absorption, increased plasma and tissue plant sterol concentrations, and low cholesterol synthesis characterize this disease. Mean total microsomal HMG-CoA reductase (rate-control controlling enzyme for cholesterol biosynthesis) activity was sevenfold higher (98.1 +/- 28.8 vs. 15.0 +/- 2.0 pmol/mg protein per min) and microsomal enzyme protein mass was eightfold larger (1.43 +/- 0.41 vs. 0.18 +/- 0.04 relative densitometric U/mg protein) in 11 controls than the average for two sitosterolemic liver specimens. HMG-CoA reductase mRNA probed with pRED 227 and pHRED 102 was decreased to barely detectable levels in the sitosterolemic livers. In addition, there was a 50% decrease in the rate [2-14C]mevalonic acid was converted to cholesterol by sitosterolemic liver slices compared with controls (112 vs. 224 +/- 32 pmol/g liver per h). In contrast, average total LDL binding was 60% greater (326 vs. 204 +/- 10 ng/mg), and high affinity (receptor-mediated) binding 165% more active (253 vs. 95.1 +/- 8.2 ng/mg) in two sitosterolemic liver membrane specimens than the mean for 12 controls. Liver morphology was intact although sitosterolemic hepatocytes and microsomes contained 24 and 14% less cholesterol, respectively, and 10-100 times more plant sterols and 5 alpha-stanols than control specimens. We postulate that inadequate cholesterol biosynthesis is an inherited abnormality in sitosterolemia and may be offset by augmented receptor-mediated LDL catabolism to supply cellular sterols that cannot be formed.